Prenatal ultrasound findings associated with PIGW variants: One more piece in the FRYNS syndrome puzzle? PIGW‐related prenatal findings. (19th July 2022) - Ronzoni, Luisa; Boito, Simona; Meossi, Camilla; Cesaretti, Claudia; Rinaldi, Berardo; Agolini, Emanuele; Rizzuti, Tommaso; Pezzoli, Laura; Silipigni, Rosamaria; Novelli, Antonio; Iascone, Maria; Persico, Nicola; et al.
Abstract: Objective: We describe the prenatal ultrasound findings and autopsy of three fetuses with multiple congenital anomalies (MCA) whose diagnostic workup suggested the same genetic etiology. We conducted a literature review to corroborate the molecular results and find evidence that the identified variants are responsible for the phenotype seen. Methods: Trio‐based Exome Sequencing (ES) analysis was performed on chorionic villus samples. We reviewed available reports dealing with prenatal manifestations of genes involved in the Glycosylphosphatidylinositols (GPI) biosynthesis defects (GPIBDs). Results: Prenatal findings shared by all the three pregnancies included facial dysmorphisms, brain malformations of the posterior fossa, skeletal and genitourinary anomalies. ES analysis identified homozygous variants of uncertain significance in PIGW in the three fetuses. Prenatal findings of the three pregnancies overlapped with those previously described for PIGW variants and with those associated with PIGN, PIGV and PIGA variants. Conclusion: Based on the phenotypic overlap between the prenatal findings in our three cases and other cases with pathogenic variants in other genes involved in GPIBDs, we speculate that the variants identified in the three fetuses are likely causal of their phenotype and that the PIGW clinical spectrum might extend to MCA, mainly involving brain, skeletal and genitourinary systems. Moreover, we suggest that also PIGW could be involved in Fryns/Fryns‐like phenotypes. Key points: What's already known about this topic? Defects in genes involved in Glycosylphosphatidylinositol biosynthetic pathway cause intellectual disability (ID), epilepsy, dysmorphic features and congenital anomalies. PIGN, PIGV and PIGA variants are associated with Fryns syndrome (FS) PIGW variants have been described to be associated with neurodevelopmental disorders. What does this study add? The prenatal phenotype of PIGW variants includes brain, skeletal and genitourinary anomalies detectable by ultrasound. PIGW variants could be involved in Fryns phenotype.